Radiation risk and human space exploration - Schimmerling, W.; Cucinotta, F.A.; Wilson, J.W. (Advances in space research, 2003)
Radiation protection is essential to enable humans to live and work safely in space. Predictions about the nature and magnitude of the risks posed by space radiation are subject to very large uncertainties. Prudent use of worst-case scenarios may impose unacceptable constraints on shielding mass for spacecraft or habitats, tours of duty of crews on Space Station, and on the radius and duration of sorties on planetary surfaces. The NASA Space Radiation Health Program has been devised to develop the knowledge required to accurately predict and to efficiently manage radiation risk. The knowledge will be acquired by means of a peer-reviewed, largely ground-based and investigator-initiated, basic science research program. The NASA Strategic Plan to accomplish these objectives in a manner consistent with the high priority assigned to the protection and health maintenance of crews will be presented.